SYMBOLIC MEANINGS OF AMONG TEBAL RITUAL IN NOVEL GENDUK BY SUNDARI MARDJUKI - Lerry Alfayanti; Sarwiji Suwandi; Retno Winarni (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
This study aims to describe the symbolic meanings of among tebal ritual and the description of attitude of life of the tobacco farmers on the slopes of Sindoro in novel Genduk by Sundari Mardjuki. This research uses descriptive qualitative method which put forward on content analysis with in-depth reading on the novel. The problem in this research is the symbolic meaning of among tebal ritual and the description of the attitude of life of the tobacco farmers on the slopes of Sindoro which is reflected from among tebal ritual in the novel Genduk. The data of this research are all symbolic expressions in among tebal ritual and all words and sentences that describe the attitude of life of the tobacco farmers on the slopes of Sindoro in the novel Genduk. Result this research can describe the symbolic meaning of among tebal ritual which consists of symbolic meaning of ritual offerings that are white, yellow, red, and black tumpeng which symbolize the four elements in human beings that cannot be separated and jajan pasar that symbolize human character in this world is different. Prayer in rituals has a high expectation for tobacco plants to be planted to grow fertile with good harvest. The symbolic meaning of the procession of among tebal ritual is the togetherness that is in the society of tobacco farmers on the slopes of Sindoro. This study describes the attitude of life of the tobacco farmers on the slopes of Mount Sindoro which reflected from among tebal.Keywords: among tebal, attitude of life, symbolic meanings, tobacco farmers MAKNA SIMBOLIK RITUAL AMONG TEBAL DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI AbstrakPenelitian ini bertujuan mendeskripsikan makna simbolik ritual among tebal dan deskripsi sikap hidup petani tembakau di lereng sindoro dalam novel Genduk Karya Sundari Mardjuki. Penelitian ini menggunakan metode kualitatif deskriptif yang lebih mengedepankan pada analisis konten (isi) dengan pembacaan mendalam pada novel. Masalah dalam penelitian ini adalah makna simbolik dari ritual among tebal serta deskripsi sikap hidup petani tembakau di lereng sindoro yang tercermin dari ritual among tebal dalam novel Genduk. Data penelitian ini berupa semua ungkapan simbolis pada ritual among tebal serta semua kata dan kalimat yang mendeskripsikan sikap hidup petani tembakau di lereng Sindoro dalam novel Genduk. Hasil penelitian ini mendeskripsikan makna simbolik ritual among tebal yang terdiri atas makna simbolik sesaji ritual yaitu tumpeng putih, kuning, merah, dan hitam yang melambangkan keempat unsur dalam diri manusia tidak dapat dipisahkan serta jajanan pasar yang melambangkan karakter manusia di dunia ini tidak ada yang sama. Doa dalam ritual memiliki makna pengharapan tinggi untuk tanaman tembakau yang akan ditanam dapat tumbuh subur dan panennya bagus. Makna simbolik prosesi ritual among tebal yaitu kebersamaan yang terjalin di masyarakat petani tembakau lereng Sindoro. Penelitian ini juga mendeksripsikan sikap hidup petani tembakau lereng Sindoro yang tercermin dari ritual among tebal.Kata kunci: makna simbolik, among tebal, sikap hidup, petani tembakau